Does the innovation-driven digital economy improve the resilience of industrial and supply chains? - Yuling Wang; Yuliang Long; Jing Wang (Journal of Innovation & Knowledge (JIK), 2025)
This study utilizes panel data from 31 Chinese provinces over the period from 2011 to 2021. The entropy method is employed to calculate comprehensive indices. An index system is developed for assessing the development level of the innovation-driven digital economy and the resilience of industrial and supply chains. We subsequently construct a panel fixed-effects regression model that incorporates entrepreneurial activity as a moderating variable. This study empirically examines how the digital economy impacts the resilience of industrial and supply chains. We also apply a spatial Durbin model to explore spatial spillover effects and regional disparities in the influence of digital economy development on chain resilience. The results show that the digital economy significantly bolsters chain resilience through increased entrepreneurial activity. Furthermore, the level of the digital economy affects the resilience of the industrial and supply chains in neighboring provinces, indicating the presence of spatial spillover effects. Additionally, the impact of the digital economy on the resilience of industrial and supply chains exhibits regional heterogeneity.
Keywords: A10; F69; 650; Innovation-driven digital economy; Industrial chain; Supply chain resilience; Moderating effects; Spatial spillover effects